Xylene isomerization over zeolite catalysts - Noordin, Mohd. Suffian; Mat, Ramli (Faculty of Chemical & Natural Resources Engineering, 1994)
Paraxylene is used as a raw material for the production of the synthetic fibers. The production of paraxylene can be obtained by isomerization of xylene using zeolites as catalyst. At equilibrium, the mixture of xylene contains 24% para, 24% ortho and 52% of metaxylene. The objective of this experiment is to access the effectiveness of several zeolite catalysts for the isomerization of xylene. The study was carried out using micro reactor packed with zeolite (0.5g). In this work, the activity and selectivity of the catalyst in the isomerization of xylene depend on the type of zeolite used. HZSM-5 catalyst gives higher activity and selectivity over other type of zeolite.